A Multi-Criteria Decision Analysis for Building Envelope Design : Bridging Moisture Safety and Health Risks - Bayat Pour, Mohsen (Indoor Environments, 2025)
Developing a robust decision analysis framework for selecting appropriate building envelope assemblies is essential to ensure moisture safety, energy efficiency, and sustainability. Recently, Bayat Pour et al. introduced the inutility decision analysis (IDA) method, which integrates moisture safety criteria with sustainability considerations, including economic and environmental aspects. This study builds upon the IDA framework by addressing a previously identified gap: the lack of occupant health analyses. A new feature is incorporated into the method to assess health impacts, specifically related to mould exposure. Three case studies of timber-framed walls were analysed under Stockholm climate conditions. The probabilistic mould reliability analysis showed that the probability of exceeding the mould index threshold (MI = 3) was 2.3 % for CS1, 0 % for CS2, and 71.5 % for CS3. Health consequence calculations linked mould occurrence to asthma and allergic rhinitis, with potential lifetime costs of 22,415 €/m² and 3,403 €/m², respectively, under worst-case conditions. The inutility decision analysis further demonstrated the trade-offs between initial and health-related costs: CS1 (SPR = 0.14) combined initial costs (45.27 €/m²) with low health inutility (279.87 €/m²); CS2 (SPR = 0.50) required the highest initial costs (180.84 €/m²) but avoided health costs entirely; CS3 (SPR = 0.59) offered the lowest initial costs (34.05 €/m²) but incurred the largest health inutility (8,815.39 €/m²). These findings illustrate how IDA can provide a transparent and balanced decision framework, moving beyond deterministic or initial costs-based assessments to explicitly address occupant health and long-term sustainability in building envelope design.
Keywords: Human health consequences; Moisture safety design; Economic aspects; Probabilistic analysis; Machine learning; Decision analysis